Making access to health care more equal: the role of general medical services. Issue 6601 (26th September 1987) - Bevan, G; Charlton, J
Abstract : The Resource Allocation Working Party (RAWP) recognised the need to consider both health authority and primary care services in achieving its objective. RAWP and the subsequent Advisory Group on Resource Allocation (AGRA) found (but did not publish) considerable variation in resources used by both services but could not find a clear relation between them. Statistics provided by the DHSS were used to compare spending by 80 area health authorities in 1980-1 with expenditure per head on general medical services by their corresponding family practitioner committees. There was considerable variation in the provision of resources for both services and no clear relation between the variations in spending on each service. Only 40 of the 80 areas had both health authority and family practitioner committee spending levels within 10% of "target." Subregional inequalities in resources tend to be related to variations in admission rates, which in turn are related to general practitioners' referral behaviour. These results emphasise the importance of finding out more about inequalities in the provision of general medical services and their relation to the use of hospital services. They also suggest that RAWP's aim of equality of opportunity of access to health care resources may be achieved only if general medical services are brought into the equation as well.